ANALISIS KELAYAKAN ISI DAN PENYAJIAN MUATAN PELAJARAN IPS PADA BUKU TEMATIK SISWA KELAS VI SEKOLAH DASAR - Ghasya, Dyoty Auliya Vilda (Universitas Negeri Surabaya, 2017)
ABSTRACTThe purposes of this research is (1) to find out the eligibility level description contents of Social lessons on the thematic book 3